Socio-Technical Modular Approach dalam In-Situ Slum Upgrading Kawasan Bantaran Sungai Kelurahan Sungai Baru, Kota Banjarmasin - Ahmad Zaki; Prananda Navitas (Dinasti Research, 2026)
Riverbank settlements in urban areas are highly susceptible to environmental degradation and climate-induced hazards. In Banjarmasin, a city characterized by its extensive river network, the proliferation of high-density slum areas along riverbanks presents a significant urban environmental challenge. The Sungai Baru neighborhood demonstrates this complexity, where inadequate spatial planning, poor sanitation infrastructure, and physical vulnerability weaken the community’s resilience against hydrometeorological risks such as tidal flooding. This study aims to formulate comprehensive spatial upgrading strategies for the riverbank slum settlement in Sungai Baru to enhance urban environmental quality and spatial resilience. This Study employed a qualitative spatial approach, combining comprehensive field observations and qualitative assessments of the existing built environment to determine slum typologies and vulnerabilities. The analysis identified key priority zones requiring immediate spatial intervention based on ecological and infrastructural constraints. The proposed strategies comprise a spatial framework for slum upgrading, including the reorganization of residential layouts, revitalization of riverbank buffers, and integration of sustainable infrastructure. Ultimately, these spatial interventions are expected to mitigate environmental hazards and function as an adaptive mechanism that contributes to a sustainable and resilient urban environment in Banjarmasin.